Question Asking Skills: Levels, Conditions, Classification, and Types (Journal Of Educational and Psychological Researches, 2022)
The research aims to know the question asking skills in terms of levels, conditions, classification, and types. The research limited to the literature that dealt with the importance of questioning for students and teachers. The most important term used in the research is the skill (Ryan defined it as "the ability to perform with great efficiency, accuracy, and ease). The results of the research are as follows: 1. the questions asked by the schoolteacher within the assessment of students' learning. 2. Teachers should focus on the lower levels of learning (remembering, understanding and comprehension) and then evaluating students at the higher levels (synthesis and evaluation). 3. Teacher with good knowledge can skillfully use the questioning inside the class. The main research recommendations are: 1. Encouraging students to ask questions through procedural patterns that help them. 2. Motivating teachers to employ all types of the question-asking skills. The most important suggestion is to conduct a questionnaire to measure the question-asking skills among teacher who teaching social subjects.